Development of Rheumatoid Arthritis in Cavitary Mycobacterium avium Pulmonary Disease: A Case Report of Successful Treatment with CTLA4-Ig (Abatacept) - Tanaka H; Asakura T; Kikuchi J; Ishii M; Namkoong H; Kaneko Y; Fukunaga K; Hasegawa N (Infection and Drug Resistance, 2022)
Hiromu Tanaka,1 Takanori Asakura,1 Jun Kikuchi,2 Makoto Ishii,1 Ho Namkoong,3 Yuko Kaneko,2 Koichi Fukunaga,1 Naoki Hasegawa3 1Division of Pulmonary Medicine, Department of Medicine, Keio University School of Medicine, Shinjuku-ku, Tokyo, Japan; 2Division of Rheumatology, Department of Medicine, Keio University School of Medicine, Shinjuku-ku, Tokyo, Japan; 3Department of Infectious Diseases, Keio University School of Medicine, Shinjuku-ku, Tokyo, JapanCorrespondence: Takanori AsakuraDivision of Pulmonary Medicine, Department of Medicine, Keio University School of Medicine, 35 Shinanomachi, Shinjuku, Tokyo, 160-8582, JapanTel +81-3-3353-1211Fax +81-3-3353-2502Email takanori.asakura@keio.jpBackground: Nontuberculous mycobacterial pulmonary disease (NTM-PD) often develops in patients with rheumatoid arthritis (RA), especially during immunosuppressive treatment, including biological disease-modifying antirheumatic drugs. NTM-PD is associated with airway lesions such as bronchiectasis, which is frequently seen in RA patients. Distinguishing which diseases cause the pulmonary lesion is difficult. However, there are limited reports of the development of RA during the follow-up of NTM-PD and how biological agents should be administered in these conditions, especially with cavitary lesions.Case Presentation: A 62-year-old woman with hemosputum was referred to our hospital, where she was diagnosed with Mycobacterium avium pulmonary disease. She began treatment with several antibiotics, including clarithromycin, ethambutol, rifampicin, and amikacin. In the course of treatment, M. avium became macrolide-resistant. Five years after beginning antibiotic treatment, she felt arthralgia in the fingers and wrists and had a high titer of rheumatoid factor and anticitrullinated peptide antibody, with which we diagnosed RA. Methotrexate, prednisolone, and iguratimod were subsequently administered, but the activity of RA gradually worsened. Meanwhile, M. avium changed to a macrolide-susceptible strain, her sputum smear results remained almost negative, and the NTM-PD disease was well controlled with antimicrobial therapy, despite her having cavitary lesions. Therefore, we started using CTLA4-Ig (abatacept). RA symptoms were substantially ameliorated. The pulmonary lesions and NTM-PD worsened mildly, but her pulmonary symptoms were stable.Conclusion: Physicians should be mindful of the etiologies of bronchiectasis, including RA, even in patients with a long-term history of treatment for bronchiectasis and NTM-PD. When NTM-PD is well controlled, even with remaining cavitary lesions, abatacept may be an option for patients with RA based on a comprehensive assessment of disease progression using NTM sputum smear/culture, computed tomography findings, and treatment response.Keywords: rheumatoid arthritis, nontuberculous mycobacterial infection, cavitary lesion, biological agent, bronchiectasis